Who is the Real Consumer in a Credit Purchase Transaction? - Suwinto Johan (Jurnal Jurisprudence, 2021)
Purpose of the study: This study aims to determine who the actual consumers are in financing purchase transactions according to the law and regulations.Methodology:The study employed a normative judicial method. Juridical methods are the research with the library data sources.Results:Consumers are end-users, not consumers who make payments or own the goods. This definition is derived from the Consumer Protection Act. This definition of the consumer must be refined in light of its practical application in society. The differences between the buyer, owner, and user of goods necessitate a comprehensive understanding.Application of this study :Consumers have the option of paying with cash or credit. They can purchase the goods with money by paying in full and taking full ownership and usage. Consumers can also purchase goods on credit or with financing. They can apply for credit to the financing institution. The goods purchased serve as collateral for funding. If the consumer fails to make a payment, the goods purchased will be withdrawn as collateral. The financing institution will determine the type of goods that can be used as collateral. The financing company will also decide on the type of financing.Novelty / Originality of this study:The definition of consumer in a credit purchase transaction.